The role of institutional communication activities at the Ministry of Hajj and Umrah in enhancing the mental image of performing Hajj and Umrah rituals - إيمان مرسي; رزان الهلال; شروق الحارثي; لجين منصور (International Journal of Social Communication, 2024)
: Study aimed to identify the role of institutional communication activities in enhancing the mental image of performing Hajj and Umrah rituals: an applied study of the opinions of a sample of employees in the Ministry of Hajj and Umrah in Makkah Al-Mukarramah. The study relied on the descriptive analytical approach, and the researchers used the questionnaire tool to collect data from a simple random sample consisting of (100) male and female employees in the Ministry of Hajj and Umrah. The results of the study concluded that the role of institutional communication activities in enhancing the mental image of performing Hajj and Umrah rituals in the Ministry was very high in general. The results also showed the extent to which institutional communication activities contributed to enhancing the mental image of performing Hajj rituals. and Umrah at a very high level, which indicates that its contribution to improving the image of Hajj and Umrah among the public is considered good in general, and the results indicated that the obstacles facing institutional communication in the Ministry were relatively high in general